On stability of the Hill's equation with damping - Cattani, C.; Grebenikov, E.A.; Prokopenya, A.N. (Нелінійні коливання, 2004)
We consider the Hill’s equation with damping describing the parametric oscillations of the torsional pendulum excited by means of varying the moment of inertia of the rotating body. Using the method of a small parameter we have calculated analytically a fundamental system of solutions of this equation in the form of power series in the excitation amplitude ε with accuracy O(ε²) and verified the conditions of its stability. In the first-order approximation in ε, we have proved that the resonance domain exists only if the excitation frequency Ω is sufficiently close to the double natural frequency of the pendulum, and the corresponding equation of the stability boundary has been obtained. Розглядається рiвняння Хiлла зi згасанням, що описує параметричнi коливання крутильного маятника, якi збуджуються змiною моменту iнерцiї тiла, що обертається. За допомогою методу малого параметра аналiтичним шляхом отримано фундаментальну систему розв’язкiв цього рiвняння у виглядi степеневих рядiв вiдносно амплiтуди збудження ε з точнiстю до O(ε²) та перевiрено виконання умов його стiйкостi. У першому наближеннi по ε доведено, що область резонансу iснує лише в областi частот збудження Ω, близьких до подвiйної власної частоти маятника, i отримано рiвняння межi областi стiйкостi.